"Izhodišče je besedilo" – o besedilih in žanrih pri pouku slovenščine - Krajnc Ivič, Mira (Jezik in slovstvo, 2024)
The initial thesis of the paper is that a high-quality selected text is at the same time suitable for ad-dressing contextual and textual or discourse themes or learning goals, and also for addressing certain themes or learning goals in the area of a language system and vocabulary (morphological, syntactic and lexical themes), but only if these linguistic themes are at the same time characteristic features of the selected source text. This means that not every text is equally suitable for addressing any linguistic theme or learning goal of language classes. Based on this starting point for language classes, the paper presents the concept of the themes Communication, Text and Genres and their groups of goals in the Slovenian curricula in primary school from the second educational period onwards and in the high school curriculum. The theoretical background is added as a clarification, which is the basis for a slightly modified communicative-pragmatic, semantic and structural-grammatical view of working with text. The paper also provides examples of proposed work with texts and genres.
Keywords: besedila; curriculum; genres; grammar texts; Slovenian language; slovenščina; slovnica; učni načrti; žanri